Development of Excel Graphical User Interface (GUI) for tracking amplitude of fault current signals - Zainol Abidin, Nursyarina (2017)
A digital protective relay for tracking of amplitude of fault can be analysed using several tools such as Matlab and Excel. The objective of this paper is to develop for tracking amplitude of fault current signal using Excel VBA. This is because Excel VBA is low cost software and widely used. The amplitude of fault current needs some analysis, commonly using DFT measurement algorithms. Excel VBA provides an easy way to perform the analysis and create graph to visualize the fault current signal. In this paper, Excel VBA has been used with several cases studies for calculating fault current, creating sinusoidal wave from data and also will be generating from amplitude and time of fault current. It can be conclude that the created GUI can save a lots of time, easy to use and reduce errors.